1999
DOI: 10.1038/sj.bmt.1702004
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial comparing the toxicity and safety of atovaquone with trimethoprim/sulfamethoxazole as Pneumocystis carinii pneumonia prophylaxis following autologous peripheral blood stem cell transplantation

Abstract: Summary:Pneumonia due to Pneumocystis carinii is an infrequent complication following autologous stem cell transplantation (ASCT) which is associated with a high mortality. Although administration of trimethoprim/sulfamethoxazole (TMP/SMX) is an effective prophylactic strategy for Pneumocystis carinii pneumonia (PCP), treatment-associated toxicity frequently results in discontinuation of therapy. We have conducted a prospective randomized trial comparing atovaquone, a new anti-Pneumocystis agent, with TMP/SMX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 13 publications
2
69
0
2
Order By: Relevance
“…11,22 Aerosolized pentamidine, atovaquone, or disulone are acceptable alternatives in case of intolerance but are probably less effective. [23][24][25][26] It should also be remembered that bone marrow toxicity is rare with the low doses of trimethoprim-sulfamethoxazole or sulfadoxinepyrimethamine used in prophylaxis, even in bone marrow recipients. 22,27 Following this study, we spread these recommendations among our team and only one case of PCP was observed during the following 2 years, as compared to 2-3 cases per year previously.…”
Section: Discussionmentioning
confidence: 99%
“…11,22 Aerosolized pentamidine, atovaquone, or disulone are acceptable alternatives in case of intolerance but are probably less effective. [23][24][25][26] It should also be remembered that bone marrow toxicity is rare with the low doses of trimethoprim-sulfamethoxazole or sulfadoxinepyrimethamine used in prophylaxis, even in bone marrow recipients. 22,27 Following this study, we spread these recommendations among our team and only one case of PCP was observed during the following 2 years, as compared to 2-3 cases per year previously.…”
Section: Discussionmentioning
confidence: 99%
“…for developing toxoplasmosis in immunocompromised patients with antibodies to Toxoplasma gondii (Machado et al, 1998). Safety and tolerability of atovaquone prophylaxis (1500 mg daily) has been demonstrated in autologous stem cell transplant recipients (Colby et al, 1999), but studies of efficacy in non-HIV-infected patients are lacking. Use of clindamycin (300 mg daily) and primaquine (15 mg daily) for prophylaxis in HIV-infected patients is associated with a higher risk for developing PCP than the TMP -SMX prophylaxis (Barber et al, 1996).…”
Section: Alternative Agentsmentioning
confidence: 99%
“…2,6 Atovaquone was generally well tolerated in patients intolerant to TMP/ SMX in that only 11% of patients were discontinued from the study. The potential benefit of TMP/SMX therapy against other pathogens will not be observed except for possible activity against toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Discontinuation of TMP/SMX therapy in up to 30% to 40% of cases had led to consideration of alternative drugs. 2,3 Atovaquone was previously shown to be effective for PCP prophylaxis at a dose of 1,500 mg once daily, 4-6 with a trend for lower efficacy at a dose of 750 mg once daily. 5 Reduced efficacy may have been related to poor tablet absorption.…”
mentioning
confidence: 99%